Strain Release Chemistry of Photogenerated Small‐Ring Intermediates. Issue 14 (15th January 2021) - Luque, Adriana; Paternoga, Jan; Opatz, Till
Abstract: Photochemical processes, such as isomerizations and cycloadditions, have proven to be very useful in the construction of highly strained molecular frameworks. Photoinduced ring strain enables subsequent exergonic reactions which do not require the input of additional chemical energy and provides a variety of attractive synthetic options leading to complex structures. This review covers the progress achieved in the application of sequences combining excitation by ultraviolet light to form strained intermediates, which are further transformed to lower energy products in strain‐release reactions. As ring strain is considerable in small ring systems, photogenerated three‐ and four‐membered rings will be covered, mainly focusing on examples from 2000 to May 2020. Abstract : Strain‐release‐driven reactions are an attractive extension of the synthetic toolbox. The strain energy contained particularly in photogenerated small ring systems provides efficient access to complex molecular scaffolds under very mild conditions. This review summarizes key strain‐release transformations of photogenerated three‐ and four‐membered ring intermediates promoted by Brønsted or Lewis acids as well as by metal‐ or photoredox catalysis. The progress made in such transformations not only concerns their sustainability but has also led to powerful methodologies suitable for the construction of natural products.